PENGARUH PENGUNGKAPAN GOOD CORPORATE GOVERNANCE DAN CORPORATE SOCIAL RESPONSIBILITY TERHADAP KINERJA PERUSAHAAN PERBANKAN - Ratna Desi Ariyani; Juniati Gunawan (LEMBAGA PENERBIT FAKULTAS EKONOMI DAN BISNIS UNIVERSITAS TRISAKTI, 2014)
This study aimed to examine the effect of GCG disclosures and CSR disclosures on banking company performance that listed on the Stock Exchange 2005-2010. Measurement of GCG disclosures using IGCG and CSR disclosures measured using ICSR. Banking company performance measured using ROA and ROE. Hypothesis testing is done using multiple regression analysis. The results showed that each GCG and CSR disclosures has significant influence on banking company performance. Percentage of GCG disclosures was tends to increase and CSR disclosures fluctuated. These mean that banking companies have started realizing the benefits of the implementing GCG and CSR. In the long term, it is expected to continue to increase the banking company performance, enjoy a good market performance that will be enjoyed by the general public.